# 8a cube +27b cube + 64c cube - 72abc

2
by shaju

2014-08-04T11:32:31+05:30
Given

We know that,

2014-08-04T12:37:00+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
factorization of 8a³ + 27b³ + 64c³ - 72 abc  ??
As the first three terms seem to be cubes of 2a, 3b, 4c respectively, we can use the formula
(x+y+z)³ = x³ + y³ + z³ + 3x² (y+z) + 3y² (z+x) + 3z² (x+y) + 6xyz
So  x³ + y³ + z³ = (x+y+z)³ -  [ 3x² (y+z) + 3y² (z+x) + 3z² (x+y) + 6xyz ]

8a³ + 27b³ + 64c³
= (2a+3b+4c)³ - [ 3 4a² (3b+4c) + 3 9b² (4c+2a) + 3 16c² (2a+3b) + 6 2a 3b 4c ]
= (2a+3b+4c)³ - [ 12a² (3b+4c) + 27b² (4c+ 2a) + 48c² (2a+3b) + 144 abc ]
8a³ + 27b³ + 64c³ - 72 abc =
=(2a+3b+4c)³ - [36a²b+48a²c+108b²c+54b²a+96c²a+144c²b+144abc]-72abc
=(2a+3b+4c)³-[(36a²b+48a²c+72abc)+(108b²c+54b²a+72abc)+(96c²a+144c²b+72abc)]
= (2a+3b+4c)³-[12a(3ab+4ac+6bc)+18b(6bc+3ba+4ac)+24c(4ca+6cb+3ab)]
= (2a+3b+4c)³- [12a+18b+24c] [3ab+4ac+6bc]
= (2a+3b+4c) [ (2a+3b +4c)² - 6(3ab+4ac+6bc) ]
= (2a+3b+4c) [ 4a²+9b²+16c²+12ab+24bc+16ac -18ab -24ac -36bc]
= (2a+3b+4c) [ 4a²+9b²+16c²-6ab -12bc - 8ac]